Zur zerebralen Organisation von Sprach - Kubiak, Paweł (Glottodidactica, 2005)
The article is devoted to the cerebral organisation of language. This work is intended as a state-of-the-art paper describing current research and theory in some subfields of cognitive neuroscience that may be of importance for the glottodidactics. Part 1 focuses on the issue of lateralization of language. Part 2 provides information on evaluation procedures in brain and points out that language, cognition and emotion can't be viewed as separate elements of mental processing. An attempt has been made to elucidate the role of epigenetic determinations in learning process. In part 3 experimental aspects of neurolinguistics are emphasized, such as aphasia research, advanced brain mapping techniques as essential steps toward better understanding the neural correlates of language functions, and a review how event-related potentials (ERPs) have been used to reflect semantic and syntactic processing in normal adults and children.